2018
DOI: 10.3390/ijerph15071549
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Way to Decrease the Know-Do Gap in Hospital Infection Control in Vietnam: “Providing Specific Figures on Healthcare-Associated Infections to the Hospital Staff Can ‘Wake Them Up’ to Change Their Behaviour”

Abstract: Adequate infection control plays a key role in preventing healthcare-associated infections (HAIs). This study aimed to explore staff perceptions of hospital infection control in a rural and an urban hospital in Vietnam. Individual interviews were conducted with hospital managers, and focus group discussions were conducted with doctors, nurses and cleaning workers separately. Content analysis was applied. An interview guide including discussion points on HAIs, hand hygiene and healthcare waste management was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
1
9
0
2
Order By: Relevance
“…Education and adherence behavior should begin in academic institutions because they are optimal environments to encourage good habits [4], since knowledge among nurses and students seems to be deficient [42], maybe due to some barriers such as allergic reactions, lack of staff, or lack of awareness [43,44,45,46]. Although traditional methods provide the necessary notions for the development of practical skills, they do not ensure the acquisition of knowledge [47].…”
Section: Discussionmentioning
confidence: 99%
“…Education and adherence behavior should begin in academic institutions because they are optimal environments to encourage good habits [4], since knowledge among nurses and students seems to be deficient [42], maybe due to some barriers such as allergic reactions, lack of staff, or lack of awareness [43,44,45,46]. Although traditional methods provide the necessary notions for the development of practical skills, they do not ensure the acquisition of knowledge [47].…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com os dados analisados, a Tabela 1 mostra o resultado quantitativo de artigos que foram localizados nas respectivas bases de dados utilizando os termos de buscas predefinidos na etapa 3 da metodologia. (GOMES et al, 2019;KIST et al, 2018;LIEN et al, 2018;PFÍTSCHER et al, 2007). Relata-se a deficiência ou a inexistência de treinamentos como fatores básicos preponderantes para o desencadeamento de possíveis impactos, assim, relatando-os em seus resultados e conclusões para que seja dada a devida significância e valorização na prevenção dos impactos (DEHGHANI et al, 2019;FERRANTE et al, 2018;GUNAWARDANA, 2018;HASAN;RAHMAN, 2018;NITIKA et al, 2017).…”
Section: Resultados E Discussõesunclassified
“…Nas infeções ou resistência de microrganismos patógenos, bem como medicamentos que interferem na resistência aos antimicrobianos, destacam-se os antibióticos (DECRAENE et al, 2018;IWERIEBOR et al, 2015;LIEN et al, 2018;RANJBAR et al, 2018;LIEN et al, 2016;SAKKAS et al, 2019;FEKADU et al, 2015;AHN;CHOI, 2016;MATHYS et al, 2019;PAULSHUS et al, 2019;NG et al, 2018;FRÓES et al, 2016;PAULSHUS et al, 2019;NG et al, 2018;KAMATHEWATTA et al, 2019;MIRANDA et al, 2015;WEN et al, 2016;CAHILL et al, 2019;MAGALHÃES et al, 2016;GALLER et al,2018;RODRIGUEZ-MOZAZ et al, 2015;GOMI et al, 2017;LE et al, 2016;SHANKARAIAH et al, 2017;MEIR-GRUBER et al, 2016;KHAN;SÖDERQUIST;JASS, 2019;MOHD;MALIK, 2018;STÅLSBY LUNDBORG et al, 2015;ALAM;IMRAN, 2018;MARATHE et al, 2019;KALAISELVI et al, 2016;HRENOVIC et al, 2019;PERINI et al, 2018).…”
Section: Resultados E Discussõesunclassified
“…Other studies stated that HCWs were not aware of the HAIs situation and own role in preventing it from avoiding infections, RTIs, and HIV through the use of unsterilized needles. Their inabilities to detect these infections were due to poor awareness of hospital staff, lack of facilities, insufficient equipment and supplies, as well as a patient overload [6]. However, the results of research from Rizk, EL-Raghi, and Zein found that although the availability of adequate facilities, based on observations time, the implementation of handwashing is still low, where only 10% of the 20 nurses wash hands [26].…”
Section: Discussionmentioning
confidence: 99%
“…In Vietnam, the staff possessed adequate knowledge, unaware of hospital infection control, including lack of resources, poor awareness, and patient overload. According to Lien, Johansson, and Lan et al that the HAIs available for health workers can improve staff awareness and put their existing knowledge into practice, thereby decreasing the know-do gap in infection control [6]. The systematic review focused on knowledge, attitude, and compliance to practice as factors impacting nurses' awareness.…”
Section: Introductionmentioning
confidence: 99%